Electrical percolation and mechanical properties of Si3N4–TiC0.5N0.5 composite ceramics - Zhu, Ming; Xia, Yongfeng; Yao, Dongxu; Zhao, Jun; Zeng, Yu‐Ping (Journal of the American Ceramic Society, 2025)
In recent years, the application of Si3N4 ceramics has been developing in the direction of structural and functional integration. In this work, highly densified Si3N4–TiC0.5N0.5 composites were fabricated by hot pressing with Y2O3–MgO sintering additives, and the effects of TiC0.5N0.5 content on phase composition, microstructure, mechanical properties, and electrical properties were studied. When the content was higher than 20 vol%, the TiC0.5N0.5 conductive network was constructed. The resistivity decreased with the increase of TiC0.5N0.5 content, and the percolation threshold was 20 vol%, where the resistivity dropped sharply by six orders of magnitude. The addition of TiC0.5N0.5 with PTC characteristic neutralized the temperature sensitivity of the resistivity of Si3N4 ceramic with NTC characteristic. Si3N4–30vol%TiC0.5N0.5 composites showed good electrical conductivity, as well as good temperature resistance stability characteristic at RT–400°C with a resistivity of 15.5 ± 2.4 Ω cm. The Si3N4–TiC0.5N0.5 composites showed relatively high mechanical properties, the flexural strength, elastic modulus, fracture toughness, and hardness of Si3N4–30vol%TiC0.5N0.5 composites were 750 MPa, 340 GPa, 6.94 MPa m1/2, and 14.8 GPa, respectively. The Si3N4‐based ceramics with integrated structural and functional properties have been obtained in this work, which is expected to be applied to sophisticated electrical devices such as electrostatic chuck, wafer heater, and infrared light source.